Optimizing Profile Videos as an Effective Promotional Tool for Branding the Photography Study Program - Purwastya Pratmajaya Adi Lukistyawan; Diana Safinda Asran; Priaji Iman Prakoso (Seni Media Rekam ISI Surakarta, 2024)
This research focuses on optimizing profile videos as an effective promotional tool to enhance the branding of the Photography Study Program at ISI Surakarta. The objective of the study is to evaluate how profile videos can increase engagement, strengthen the program's identity, and expand promotional outreach. A mixed-methods approach was employed, involving surveys, observations, and data analysis related to promotional activities. The findings indicate that profile videos featuring student testimonials, achievements, creative activities, and advanced facilities successfully enhance the program's appeal and provide comprehensive information to prospective students and stakeholders. The videos are distributed through strategic platforms, such as social media, official websites, and promotional events, ensuring a broader audience reach. It is recommended that the study program periodically update the content and utilize interactive technologies to enhance engagement in the future.